2016
DOI: 10.1007/s00508-016-1005-x
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of multidrug-resistant Proteus mirabilis in a long-term care facility in Croatia

Abstract: This is the first report of multidrug resistant P. mirabilis in a nursing home in Croatia. Cephalosporin resistance was due to plasmid-mediated AmpC β-lactamase CMY-16.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 31 publications
(53 reference statements)
1
7
0
Order By: Relevance
“…Rep-PCR (GTG) typing of forty catheter isolates in this study showed 39 types, of which two isolates from one hospital were put in one GTG type (GTG8) with 100% identity, which could be due to the dissemination of the isolates from the hospital environment to patients by personnel or nurses or nosocomial infection, and other isolates were put in single GTG type, which demonstrated high diversity among isolates. Rep-typing results show high discriminatory power, being completely in agreement with the study conducted by Bedenic et al [ 55 ]. The study typing did not confirm the previous research conducted by Michelim et al [ 56 ].…”
Section: Resultssupporting
confidence: 91%
“…Rep-PCR (GTG) typing of forty catheter isolates in this study showed 39 types, of which two isolates from one hospital were put in one GTG type (GTG8) with 100% identity, which could be due to the dissemination of the isolates from the hospital environment to patients by personnel or nurses or nosocomial infection, and other isolates were put in single GTG type, which demonstrated high diversity among isolates. Rep-typing results show high discriminatory power, being completely in agreement with the study conducted by Bedenic et al [ 55 ]. The study typing did not confirm the previous research conducted by Michelim et al [ 56 ].…”
Section: Resultssupporting
confidence: 91%
“…The most prevalent ESBL type in P. mirabilis is TEM-52, which efficiently hydrolyses aztreonam and ceftazime [ 93 ]; however, TEM-21 was identified among urinary isolates in France [ 53 ]. Among pAmpC, CMY-16 producing P. mirabilis was reported to cause outbreaks in long-term care facilities in Italy and Croatia [ 94 , 95 ]. In both reports, the isolates were clonally related and resistant to all β-lactams except cefepime and carbapenems.…”
Section: Resistance “Snapshot” In Other Notable Gram-negative Urinary Tract Pathogensmentioning
confidence: 99%
“…This is because of the production of plasmid mediated-AmpC beta-lactamase, which hydrolyzes all beta lactams except fourth generation cephalosporins and carbapenems. The strains resistant to the third-generation cephalosporins were positive for CMY-16 ( 19 ).…”
Section: Resultsmentioning
confidence: 99%